PORT MANAGEMENT CHALLENGES TOWARD SMART PORT TRANSFORMATION IN THE INDUSTRY 4.0 ERA: A QUALITATIVE CONTENT ANALYSIS (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Introduction: Smart port transformation has become a strategic issue in the Industry 4.0 era because port performance increasingly depends on digital integration, automation, data connectivity, and collaborative governance. In Indonesia, this transformation is important for improving maritime connectivity, logistics efficiency, and port competitiveness. This study examines how port management challenges toward smart port transformation are framed in official and scholarly documents. Novelty: This study provides a management-oriented perspective by focusing not only on technology, but also on governance, human resources, regulation, system integration, and operational readiness. Methods: This study used qualitative content analysis. Data were collected from selected regulations, Pelindo and Ministry of Transportation documents, official digitalization reports or news, annual or performance reports, and recent scientific articles. The data were analyzed through coding, categorization, and thematic interpretation. Results: The findings indicate that smart port transformation faces key challenges related to digital infrastructure, information system integration, human resource competence, regulatory coordination, investment capacity, cybersecurity, and operational efficiency. Conclusion: Smart port transformation requires more than technological adoption. It demands integrated port management, strong institutional coordination, adaptive human resources, and sustainable digital governance. The study implies that policymakers and port operators need to strengthen management capacity to accelerate smart port readiness in Indonesia.